Understanding the Knowledge, Attitude and Behaviour (Practice) of Saudi Arabian Patients with Diabetes Type 2 - Alqahtani, Abdulrahman Habash (Curtin University, 2019)
This qualitative study explored knowledge, attitude and practices of male T2DM patients in rural and urban populations of Riyadh, Saudi Arabia. Participants included 40 male patients aged 35 to 65 years with T2DM and 20 health care providers from rural and urban areas. Using a Grounded Theory approach three models were developed to describe the influences of T2DM management for rural patients; for urban patients and the perspectives of health care providers on T2DM management.